2022
DOI: 10.3390/rs15010019
|View full text |Cite
|
Sign up to set email alerts
|

Applying Variable Selection Methods and Preprocessing Techniques to Hyperspectral Reflectance Data to Estimate Tea Cultivar Chlorophyll Content

Abstract: Tea is second only to water as the world’s most popular drink and it is consumed in various forms, such as black and green teas. A range of cultivars has therefore been developed in response to customer preferences. In Japan, farmers may grow several cultivars to produce different types of tea. Leaf chlorophyll content is affected by disease, nutrition, and environmental factors. It also affects the color of the dried tea leaves: a higher chlorophyll content improves their appearance. The ability to quantify c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…In studies examining machine learning techniques, the Cubist algorithm has been shown globally to perform the best [37]. This excellent record of performance was also observed in the evaluation of vegetation properties based on reflectance data [23,24]. More recently still, deep-learning-based regression methods have gained in popularity for use in modeling complex relationships and making accurate predictions across various domains.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In studies examining machine learning techniques, the Cubist algorithm has been shown globally to perform the best [37]. This excellent record of performance was also observed in the evaluation of vegetation properties based on reflectance data [23,24]. More recently still, deep-learning-based regression methods have gained in popularity for use in modeling complex relationships and making accurate predictions across various domains.…”
Section: Introductionmentioning
confidence: 86%
“…Recently, affordable, compact, fingertip-sized spectrometers (such as the C12880MA [Hamamatsu Photonics]) have been developed. These small devices can be attached to unmanned aerial vehicles for conducting measurements over large areas [23,24]. However, the measurements from these sensors contain various degrees of noise and may exhibit shifts.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4e shows the spectral image after first-order derivation (D1) processing. This method highlights the rate of change in the peaks and facilitates peak detection and identification [27]. Figure 4f shows the spectral image after the second-order derivative (D2) processing, which highlights the curvature of the peaks and facilitates peak detection and identification [28].…”
Section: Changes In Fatty Acid Values Of Corn During Aging and Sample...mentioning
confidence: 99%